Recycled Construction and Demolition Wastes as filling material for geosynthetic reinforced structures. Interface properties. (15th June 2016) - Vieira, Castorina Silva; Pereira, Paulo M.; Lopes, Maria de Lurdes
Abstract: Construction and Demolition Wastes (C&DW) are increasingly being reused in civil engineering applications, mainly in concrete production and base layers of roadway infrastructures. However, frequently the fine grain portion of these recycled aggregates is not considered suitable for those applications being landfilled instead of recycled. Moreover, the value-added utilisation of recycled C&DW in the construction of geosynthetic reinforced structures (steep slopes and retaining walls) is almost an unexplored field. This research assesses the feasibility of using fine-grain recycled C&DW as filling material of geosynthetic reinforced structures (GRS), appraising the physical, mechanical and environmental characterization of the construction and demolition material (C&DM), as well as, the direct shear and pullout behaviour of the interfaces between this material and three distinct geosynthetics (two geogrids and one geocomposite reinforcement or high strength geotextile). Direct shear tests results have shown that fine-grain recycled C&DW, properly compacted, exhibit similar shear strength to natural soils used commonly in the construction of GRS. The potential contamination of groundwater by these recycled C&DW was evaluated through laboratory leaching tests and, excepting the values of sulphate and total dissolved solids (TDS), this recycled C&DW complies with the provisions of European Council Decision 2003/33/EC for inert materials. High values of coefficients of interaction for C&DW/geosynthetic interfaces, a parameter of utmost importance in the design and performance of GRS, were achieved. The results herein presented support the viability of using these recycled C&DW as filling material for GRS construction.